Inhaled versus Oral Steroids In Adults with Chronic Asthma: A Systematic Review of Therapeutic Equivalence - R.J. Mash; A. Bheeki; P. Jones (South African Family Practice)
Objectives: To determine the therapeutically equivalent doses of inhaled versus oral steroids in the treatment of adults with chronic asthma. Search strategy: The Cochrane Collaboration Airways Group conducted a search in MEDLINE ( 1966-1999), EMBASE (1980-1999) and CINAHL (1982-1999), The search included CENTRAL a database containing potential Randomised Controlled Trials (RCT) obtained by hand searching of journals within the Cochrane Collaboration. Selection criteria: Randomise controlled trials of at least 4 week duration were selected and include persons over the age of | 5 years with chronic asthma. Trials which compared inhaled steroids and oral prednisolone or prednisone were considered; the maximum daily dose for inhaled steroids was 2000 mcg and for oral steroids was 60 mg. Data collection analysis: Two independent reviewers screened 1285 titles and abstracts from the electronic search. From the result of the screened electronic search, bibliography searches and other contacts, the reviewers independently selected 15 trials of which 10 met previously defined inclusion criteria. The two reviewers independently abstracted study characteristics, and outcome measures. Main results: All trials were small and no data could be pooled. Data from six trials produced the same pattern, in which prednisolone 7.5 - 12 mg/day appeared to be as effective as inhaled steroid 300-2000 mcg/day. In two trials, inhaled steroid 300-400 mcg/day was more effective than prednisolone 5 mg/day. All doses of inhaled steroid appeared to be more effective than alternate day doses of prednisolone up to 60 mg on alternate days. Reviewers' conclusions: A daily dose of prednisolone 10 mg/day appears to be equivalent to moderate-high dose inhaled corticosteroids. Alternate-day doses of oral steroids and doses 5 mg/day appear to be less effective than low-moderate dose inhaled steroids.